2016
DOI: 10.1155/2016/9542942
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Performance of Cu-Based Coins in Artificial Sweat

Abstract: The performance of different Cu-based coins in artificial sweat was evaluated. The electrochemical behavior of the coins was determined by potentiodynamic polarization curves, linear polarization resistance, and electrochemical impedance spectroscopy. Regardless of the chemical composition of the Cu-based coins, they showed similar polarization curves; particularly, the observed similarity in the anodic zone suggests that the corrosion mechanism is the same in all cases. The presence of Ni and Zn does not appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Furthermore, the overall trend suggests that corrosion occurred almost immediately with an anodic current and continued in a uniform fashion until the maximum potential of the scan was reached. While the compositions of the simulated sweat solutions differed slightly, the overall trends for the C71300, C77000 and C77D are consistent with those reported in the literature [31,32,37]. As was noted earlier, these results may be more indicative of the lack of ionic species in this solution than an indication of the performance in service.…”
Section: Prototype Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the overall trend suggests that corrosion occurred almost immediately with an anodic current and continued in a uniform fashion until the maximum potential of the scan was reached. While the compositions of the simulated sweat solutions differed slightly, the overall trends for the C71300, C77000 and C77D are consistent with those reported in the literature [31,32,37]. As was noted earlier, these results may be more indicative of the lack of ionic species in this solution than an indication of the performance in service.…”
Section: Prototype Characterizationsupporting
confidence: 88%
“…Previous work to quantify the corrosion mechanisms associated with Cu-base alloys found the corrosion behavior highly dependent on the solution in which the behavior is characterized [2932]. The most recent work by Porcayo-Calderon [32] showed that in Cu-Ni-Zn alloys the corrosion performance is function of the Zn/Ni ratio, with an increasing ratio improving the corrosion performance. Prior research by US Mint [2, 13] identified the C77000 alloy, which has a Zn/Ni ratio of 27/18 ratio, as having acceptable corrosion-wear resistance behavior based on steam testing.…”
Section: Model Developmentmentioning
confidence: 99%
“…The second time constant was observed in the high intermediate frequency region with a phase angle which was not approaching 0 • , and the maximum phase angle was ~58 • at approximately 300 Hz. This time constant, at the intermediate frequency region, may correspond to the presence of the viscous film on the alloy's surface, and could be associated with the formation of a corrosion product on the alloy's surface [12,21,22].…”
Section: Resultsmentioning
confidence: 98%
“…Human sweat has a complex composition (different types of electrolytes, organic acids, carbohydrates, amino acids, etc.) [12,13], which varies greatly in the function of different physical, environmental, and pharmacological conditions, such as age and sex, body weight, general body condition, etc. Human saliva, like sweat, can vary a lot in its composition, also depending on the age and gender of the patient, but oral hygiene and eating habits, such as the time of day, often have an additional effect [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…(Ruan et al., 2017; Sun, Li, & Xu, 2013) Both of these triboelectric layers are attached with copper films which operate as electrodes. Copper was chosen to be the electrodes because of its higher resistance to corrosion by human sweat from the skin (Porcayo‐Calderon, Rodríguez‐Díaz, Porcayo‐Palafox, & Martinez‐Gomez, 2016; Sykes & Bond, 2013). Besides Cu is very suitable for electrode application due to its high conductivity (Abdullah, Flores, et al., 2020).…”
Section: Materials and Characterizationmentioning
confidence: 99%